Charge states and energy convertion in atomic and molecular cryocrystals - Bondybey, V.E.; Khyzhniy, I.V.; Savchenko, E.V. (Хабаршы. Физика сериясы, 2015)
In spite of detailed investigation of electronic excitations in atomic and molecular cryocrystals [1,2] the properties and dynamics of charge states, accumulation of uncompensated charge in the samples remained almost unexplored. Our group developed special techniques for investigation of charge states in cryocrystals. It was applied to rare gas solids and solid nitrogen. The correlated in real time measurements of spectrally resolved thermally stimulated luminescence, exoelectron emission, and the desorption yield were performed in combination with cathodoluminescence.Condensed noble gases as well as solid nitrogen are used as detectors of ionizing radiation and moderators. Interest in research of solid nitrogen is associated with the prospect of its application as a high energy-density material. Investigation of radiation effects in solid nitrogen and rare gas solids is of high interest for astrophysics.